Grupo teatral Ibilce (en)cena - Akinaga, Mônica Mayumi [UNESP] (2015)
From a previous selection of participants of the theater workshop, there is the formation of the theater group “Ibilce (en)cena”. This group meets to study texts and mounting plays to present in IBILCE events and institutions in this region. In 2015, the group presented the remake of “Coração Materno: Um melodrama radiofônico” which had been presented in 2014 with a different cast. Currently, the group is studying texts for mounting the next play, which will be presented in the second semester.